Strengthening Islamic Legal Literacy for Indonesian Migrant Workers in Kuching: Efforts to Ensure Legal Protection and Certainty through Community Service Activities - Ya` Rakha Muyassar; Yuko Fitrian; Sy Muhammad Ridho Rizki Maulufi Alkadrie; Sofyan Munawar, S.H.I., M.H. - (Jurnal Pengabdian Masyarakat (Bisma), 2025)
Indonesian Migrant Workers (PMI) in Kuching, Malaysia, often face various legal issues related to employment contracts, unpaid wages, inhumane working conditions, and discriminatory treatment. A lack of understanding of their legal rights—both under national and Islamic law—weakens their position in resolving these problems effectively. This Community Service Program (PKM) aims to strengthen the Islamic legal literacy of PMI through educational and participatory approaches. The objective is to raise legal awareness, empower workers to claim their rights lawfully, and promote fair and humane working environments rooted in the principles of maq??id al-shar?‘ah.The implementation method includes a preliminary survey (pre-test) to assess the participants’ baseline understanding of their rights, followed by Islamic law-based legal counseling and interactive discussion sessions. The materials emphasize key principles such as justice (al-‘adl), protection of life (?if? al-nafs), and protection of property (?if? al-m?l)—core objectives of Islamic law. A practical Islamic legal literacy module was also developed to support independent learning among PMI. The final evaluation (post-test) showed a significant increase in participants’ understanding of Islamic legal principles and their rights as workers in a cross-border context. This activity demonstrates that an Islamic values-based legal approach can serve as an effective alternative in educating and empowering migrant workers. It also strengthens the legal protection system that has often been inadequate. Furthermore, this program presents a collaborative model involving academics, migrant worker communities, and support institutions to establish a more inclusive, humane, and transformative framework of legal protection.